2016
DOI: 10.2166/wst.2016.334
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in permeation and fouling resistance of PVC ultrafiltration membranes via addition of Tetronic-1107 and Triton X-100 as two non-ionic and hydrophilic surfactants

Abstract: Two non-ionic and hydrophilic surfactant additives, Tetronic-1107 and Triton X-100, were added to poly(vinyl chloride)/NMP polymeric solution to prepare ultrafiltration membranes via immersion precipitation. Surfactants at three different weight percentages up to 6 wt% were added, and the fabricated membranes were characterized and their performance for water treatment in the presence of bovine serum albumin (BSA) as a foulant was assessed. The scanning electron microscopy images indicated remarkable changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…According to morphology analysis performed by ESEM (section ), immobilization of TRX/gA does not affect membrane porosity. It has been reported that exposure to the surfactant enhances wetting properties of polymeric membranes and can enhance water uptake properties, which is observed also in the present case.…”
Section: Results and Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…According to morphology analysis performed by ESEM (section ), immobilization of TRX/gA does not affect membrane porosity. It has been reported that exposure to the surfactant enhances wetting properties of polymeric membranes and can enhance water uptake properties, which is observed also in the present case.…”
Section: Results and Discussionsupporting
confidence: 82%
“…The influence of Triton X100 (TRX) on the water flux properties of the polymeric membranes has been previously reported, and it was found that treatment with a surfactant significantly enhances water passage through the polymeric membranes. Because the water flux is expected to increase after treatment with Triton solution, overall ion passage is going to increase as well. Because TRX treatment and TRX/gA micelle immobilization imply interaction of the membrane surface with the surfactant, we expect both modifications to improve ion permeability.…”
Section: Results and Discussionmentioning
confidence: 99%
“…UF membranes have been produced by different polymers such as polysulfone (PSf), cellulose acetate (CA), polyethersulfone, polyacrylonitrile, polyetherimide (PEI), poly(vinylidene fluoride), and poly(vinyl chloride) (PVC) . However, between these materials, PVC is an outstanding polymer for the fabrication of UF membranes because of its interesting good characteristics, including stiffness, lower price, excellent physical properties and mechanical performance, and good thermal stability.…”
Section: Introductionmentioning
confidence: 99%